Optimal Power Flow Enhancement Considering Contingency with Allocate FACTS - Lubis, Rakhmad; Hadi, Sasongko Pramono; Tumiran, Tumiran (2013)
This paper presents techniques for OPF-based electricity market enhancement with considering contingencies, allocating the Flexible AC Transmission System (FACTS) and estimating the system-wide available transfer capability (SATC) computations. The voltage stability constraints optimal power flow (VSC-OPF) problem formulation installs with the FACTS and includes the loading parameter in order to ensure enhancement a proper stability margin for the market solution. The first technique is an iterative approach and computes the SATC value based on the